Penyuluhan tentang Bahaya Merokok SMA Negeri 2 Sampoiniet Kecamatan Sampoiniet Kabupaten Aceh Jaya - Wildan Seni; Winda Sarnika; Rusdi Rusdi (Pusat Riset dan Inovasi Nasional, 2025)
Tobacco consumption is one of the health challenges in Indonesia and is very important for this country, where according to data from the 2023 Indonesian Health Survey (SKI) conducted by the Ministry of Health (Kemenkes), the number of active smokers is estimated to reach 70 million people, with 7.4% of them being smokers aged 10-18 years. The health impacts caused by cigarettes span generations, causing two-thirds of Indonesian children to be exposed to cigarette smoke, this exposure contributes to stunting and inhibits development in childhood (WHO, 2020). This study was conducted in January 2024 with the research subjects being 39 students in grades X, XI and XII of SMAN 2 Sampoiniet, Aceh Jaya Regency. Methodologically, there are two data collection techniques that will be used in this study, namely by distributing questionnaires before explaining the material and after explaining the material. Thus, the researcher's error rate can be minimized as much as possible and the percentage of answering is higher. Interviews were conducted informally. In this way, the information obtained is expected to be more abundant, in-depth, and more descriptive of the actual situation. The results of the study showed that there was an increase in students' knowledge before being given counseling, namely 20.5% and after being given counseling, namely 46.2%. The level of students' knowledge before and after being given counseling experienced a significant increase, namely 20.5 <46.2.